Complications associated with intravesical migration of an intrauterine device - Athar Rasekhjahromi; Zohre Chitsazi; Azadeh Khlili; Zahra Zarei Babaarabi (Korean Society of Obstetrics and Gynecology, 2020)
The intrauterine device (IUD) is the most common method of reversible contraception in women. However, IUD can perforate the uterus and also migrate into pelvic or abdominal organs. A 43-year-old woman with a 5-year history of IUD placement and without specific symptoms, decided to remove her IUD and undergo tubal ligation. Radiological assessment, including a pelvic X-ray and ultrasonography, revealed no copper IUD within the uterus. Retrieval attempts with cystoscopy were unsuccessful. The IUD was found embedded in the fundal part of the bladder wall and was subsequently removed through a laparotomy incision. Although there are cases in the literature that were successfully managed with cystoscopy, in chronic cases, the formation of granulation tissue may preclude retrieval of an IUD using this intervention.